Mind maps as a method of generating and structuring ideas in the learning process - Шаханова, Г (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This article discusses the method of mapping thinking as a way to effectively use the brain’s ability to perceive, memorize, analyze, express and control information. The method of mapping thinking can be used where you need to display and organize a variety of information. Intellect cards can be used in a variety of situations and for different purposes. The article gives a step-by-step instruction on the compilation of the intellect card. The advantages and disadvantages of using intelligence cards in the educational process are described. The author shows that the intelligence cards allow not only to improve the quality of learning by students, but also to optimize and organize the learning process and self-study. The article describes the methods of organizing training using mind maps. It is concluded that the mind map can be considered as a method of generating and structuring ideas in the learning process.